SISTEM KERJA BURUH BONGKAR MUAT OLEH KOPERASI TENAGA KERJA BONGKAR MUAT DI PELABUHAN BOOM BARU PALEMBANG - Geeta Fedriani; Defran Winanda (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
Loading and unloading labor is one of the most important factors in supporting the success of loading and unloading activities at the port. The availability of loading and unloading labor with sufficient skills and with the right amount is always the goal of the loading and unloading. The formulation of the problem to be discussed is how the labor loading and unloading work system by the Unloading Labor Cooperative at the Boom Baru Port of Palembang. This research is a qualitative study using primary data through field observations and interviews with qualitative descriptive analysis. Unloading / Loading Workers or Unloading Workers at Boom Baru Palembang have a work system consisting of two shifts, with a count of 1 shift will work for 8 hours cut 1 hour rest ie shift 1 from 08.00 to 16.00 WIB and shift 2 from 16.00 to 24.00 WIB, and wages will be paid after the loading and unloading works are completed.